The effect of long-term disinfection procedures on hardness property of resin denture teeth - Campanha, Nara Hellen; Pavarina, Ana Claudia [UNESP]; Jorge, Janaina Habib [UNESP]; Vergani, Carlos Eduardo [UNESP]; Machado, Ana Lucia [UNESP]; Giampaolo, Eunice Teresinha [UNESP] (Wiley-Blackwell, 2012)
Objective: The aim of the study was to evaluate the effect of long-term disinfection procedures on the Vickers hardness (VHN) of acrylic resin denture teeth.Material and methods: Five acrylic resin denture teeth (Vipi Dent Plus-V, Trilux-T, Biolux-B, Postaris-P and Artiplus-A) and one composite resin denture teeth (SR-Orthosit-O) were embedded in heat-polymerised acrylic resin within polyvinylchloride tubes. Specimens were stored in distilled water at 37 degrees C for 48 h. Measurements of hardness were taken after the following disinfection procedures: immersion for 7 days in 4% chlorhexidine gluconate or in 1% sodium hypochlorite (CIm and HIm group, respectively) and seven daily cycles of microwave sterilisation at 650 W for 6 min (MwS group). In the WIm group, specimens were maintained in water during the time used to perform the disinfection procedures (7 days). Data were analysed with ANOVA followed by the Bonferroni procedure (alpha = 0.01).Results: Microwave disinfection decreased the hardness of all acrylic resin denture teeth (p < 0.001). Immersion for 7 days in 4% chlorhexidine gluconate or distilled water had significant effect on the hardness of the acrylic resin denture teeth A (p < 0.01), and 1% sodium hypochlorite on teeth T (p < 0.01). All disinfection procedures decrease the hardness of the composite resin denture teeth (p < 0.01). Teeth O exhibited the highest and teeth V the lowest hardness values in the control group (p < 0.01).Conclusions: Disinfection procedures changed the hardness of resin denture teeth.
Keywords: acrylic resin denture teeth; Vickers hardness; acrylic resin dentures; sterilisation